RANCANG BANGUN ALAT FILTRASI PENYEDIA AIR SIAP MINUM DENGAN SISTEM REVERSE OSMOSIS - Sumirat, Nariah R.; Ali, Mukhlis (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
Drinking water is a very basic basic need, and cannot be replaced by other elements. The needs of living things for drinking water are very many, not only needed by humans but also needed by animals and plants. To produce good and quality drinking water in accordance with health standards that have been set by the Regulation of the Minister of Health of the Republic of Indonesia No. 492 / MENKES / PER / IV2010, a proper water treatment process is needed. This research activity is aimed at designing a filtration device that is able to process dirty water into clean ready-to-drink water using reverse osmosis (RO) technology. The parameters tested are biological, physical, and chemical parameters in accordance with the requirements for good drinking water set by Permenkes No. 492 of 2010. This study used 3 water source samples to be tested, namely: the first sample was a relatively clear and odorless water sample but the bacteria content was above the standard, the second sample was turbid but odorless water, while the third sample was odorous water. After going through the filtration process with the tool made, ready-to-drink water is able to be produced with the condition that the bacterial level (total coliform) drops from 200/100ml to 0/100ml. In addition, the turbidity level also dropped from 8 NTU to 0 NTU, and the water condition also changed from smelly to odorless. So it can be concluded that the filtration device made and tested is able to produce readyto-drink water according to the standards of Permenkes No. 492 of 2010.